Tissue Engineering Meets Nanotechnology: Molecular Mechanism Modulations in Cornea Regeneration - Olja Mijanović (MDPI AG, 2021)
Nowadays, tissue engineering is one of the most promising approaches for the regeneration of various tissues and organs, including the cornea. However, the inability of biomaterial scaffolds to successfully integrate into the environment of surrounding tissues is one of the main challenges that sufficiently limits the restoration of damaged corneal tissues. Thus, the modulation of molecular and cellular mechanisms is important and necessary for successful graft integration and long-term survival. The dynamics of molecular interactions affecting the site of injury will determine the corneal transplantation efficacy and the post-surgery clinical outcome. The interactions between biomaterial surfaces, cells and their microenvironment can regulate cell behavior and alter their physiology and signaling pathways. Nanotechnology is an advantageous tool for the current understanding, coordination, and directed regulation of molecular cell–transplant interactions on behalf of the healing of corneal wounds. Therefore, the use of various nanotechnological strategies will provide new solutions to the problem of corneal allograft rejection, by modulating and regulating host–graft interaction dynamics towards proper integration and long-term functionality of the transplant.